PEMBEDAAN JENIS KELAMIN AEDES AEGYPTI (DIPTERA:CULICIDAE) BERDASARKAN MORFOMETRI SAYAP - Abdul Gafur (Bioscientiae, 2006)
Morphometric analysis has been applied on wing venation of Aedes aegypti in search for sex discriminating characters. Based on Cartesian coordinates of termination and branching points on wings, interpoint Euclidean distances were measured and standardized by distances reflecting width and length of wing. Stepwise discriminant analyses found three distances relative to wing width which, by cross validation, could discriminate male and female Aedes aegypti with a high success rate (94.6%). This demonstrated that wing venation could be used in sex discrimination of Aedes aegypti mosquitoes. The finding would contribute to identification or discrimination of populations of Aedes aegypti using wing measurements as the latter approach can only be applied on exclusively male or female specimens.